ปัจจัยที่มีผลต่อความพึงพอใจในการทำงานของพนักงานกลุ่มเจนเนอเรชั่นวาย บริษัท ไทยรวมสินพัฒนาอุตสาหกรรม จำกัด - อรนนท์ ปรังฤทธิ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objective of this independent study was to study work satisfaction of generation Y employees towards Thaiunion Manufacturing Company Limited. The samples were 308 generation Y employees. The tool for collecting data was questionnaire. The data was analyzed using descriptive statistics, namely frequency, percentage, mean, and multiple regression analysis. The results of the study showed that the number of female and male employees were at similar. Most employees (43.18%) were 29-32 years old, single, with Bachelor’s degree. Their work period was less than or not exceeding 5 years. Their positions were staff or technician at Engineer Unit 1. Their monthly income was less than or not exceeding 15,000 baht. The employees showed medium level of overall satisfaction towards work. Their satisfaction towards motivation factors was at the medium level, in the following order: success, nature of work, responsibility, respect, and progress, respectively. Their satisfaction towards supporting factors was at the medium level, in the following order: stability, position, policy and administration, governance, privacy, relationship with their supervisor/subordinates/co-workers, finance, and work situation, respectively.